Modern approaches to management of diversified corporations (Путеводитель предпринимателя)
In article the latest tendencies in development of the modern theory and practice of management by diversified corporations are considered. It is shown that today theproblem of formation of competitive model of corporate management is nominated to the forefront on the basis ofwide use ofscientific approaches to the organization ofadministrative activity.